157k views
4 votes
Let g(x)=2x and h(x)=x^2+4. evaluate (h o g)(-3)

User Alleyne
by
5.9k points

2 Answers

5 votes

Answer:


\boxed{(h \circ g)(-3) = 40}.

Explanation:

By the definition of function composition, we have:


(h \circ g)(-3) = h[g(-3)].

Since
g(x) = 2x, we get:


g(-3)=2*(-3) = -6.

On the other hand, since
h(x) = x^2+4, we have:


h[\underbrace{g(-3)}_(=-6)] = h(-6) = (-6)^2 + 4 = 36 + 4 = 40.

So we finally get:


\boxed{(h \circ g)(-3) = 40}.

User Artyom Tsoy
by
5.4k points
3 votes


g(x)=2x\\\\h(x)=x^2+4\\\\(h\circ g)(x)=(2x)^2+4=4x^2+4\\\\(h\circ g)(-3)\to\text{put x = -3 to the equation of the function}\\\\(h\circ g)(-3)=4(-3)^2+4=4(9)+4=36+4=40\\\\Answer:\ \boxed{(h\circ g)(-3)=40}

User RoundPi
by
6.2k points